2016
DOI: 10.1016/j.chest.2016.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Factor Xa Inhibitor Rivaroxaban Passes Into Human Breast Milk

Abstract: Thromboembolic disorders frequently require antithrombotic treatment during pregnancy and lactation. Vitamin K antagonists and heparins are the treatment options of choice in breastfeeding women. Factors including the route of administration, discomfort during treatment, and fetal and neonatal safety affect women's choices about anticoagulant therapy. Direct-acting oral anticoagulants (DOACs) have emerged as alternatives to these agents and may offer advantages compared with vitamin K antagonists. As breastfee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…DOACs would, once again, provide an attractive alternative to traditional anticoagulants during the puerperium. Animal studies from all the direct factor Xa inhibitors suggest that they will transfer into breastmilk and, for rivaroxaban, a single case report has confirmed this to be the case in humans (Wiesen et al , ). No animal data for dabigatran exists, however data from the Dalmation study [Eudra CT 2014‐004249‐29] has recently posted results from two subjects of their open‐label phase II clinical trial of dabigatran in breastfeeding women, which suggest that dabigatran does transfer into breastmilk [available at https://www.clinicaltrialsregister.eu/ctr-search/trial/2014-004249-29/results].…”
Section: Women's Health and Treatment Of Vtementioning
confidence: 97%
“…DOACs would, once again, provide an attractive alternative to traditional anticoagulants during the puerperium. Animal studies from all the direct factor Xa inhibitors suggest that they will transfer into breastmilk and, for rivaroxaban, a single case report has confirmed this to be the case in humans (Wiesen et al , ). No animal data for dabigatran exists, however data from the Dalmation study [Eudra CT 2014‐004249‐29] has recently posted results from two subjects of their open‐label phase II clinical trial of dabigatran in breastfeeding women, which suggest that dabigatran does transfer into breastmilk [available at https://www.clinicaltrialsregister.eu/ctr-search/trial/2014-004249-29/results].…”
Section: Women's Health and Treatment Of Vtementioning
confidence: 97%
“…98 Wiesen et al capitalized on a rare situation when a lactating woman was diagnosed with a lower extremity VTE in their hospital. 99 The patient had ceased breastfeeding due a postpartum cardiomyopathy and was treated initially with enoxaparin followed by rivaroxaban. 99 During weaning, breast milk samples were collected for analysis of rivaroxaban levels.…”
Section: Doacs In Pregnancy and Lactationmentioning
confidence: 99%
“…99 The patient had ceased breastfeeding due a postpartum cardiomyopathy and was treated initially with enoxaparin followed by rivaroxaban. 99 During weaning, breast milk samples were collected for analysis of rivaroxaban levels. 99 Rivaroxaban concentration in the milk reached 40% of the plasma drug concentration, with the estimated relative infant dose to be 1.3%-well below the proposed acceptable 10% exposure concentration.…”
Section: Doacs In Pregnancy and Lactationmentioning
confidence: 99%
“…A recent case study aimed to assess the concentration of rivaroxaban in the breast milk of a single woman in the beginning of the lactation period. It showed that rivaroxaban was able to pass into breast milk but conclusions regarding the infant's exposure cannot be drawn based on a single case and without assessing the infant's plasma or urine rivaroxaban concentrations [65].…”
Section: B) Rivaroxabanmentioning
confidence: 99%